2022
DOI: 10.1073/pnas.2113386119
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonate production by marine microbes: Exploring new sources and potential function

Abstract: Significance Phosphonates are a class of phosphorus metabolites characterized by a highly stable C-P bond. Phosphonates accumulate to high concentrations in seawater, fuel a large fraction of marine methane production, and serve as a source of phosphorus to microbes inhabiting nutrient-limited regions of the oligotrophic ocean. Here, we show that 15% of all bacterioplankton in the surface ocean have genes phosphonate synthesis and that most belong to the abundant groups Proch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 120 publications
4
52
0
Order By: Relevance
“…Indeed, it has also been found that natural BPs, such as ciliatin or 2-aminoethylphosphonic acid (2-EPA), which are analogs of the amino acids β-alanine and aminosulfonate taurine, are quite common among different organisms, from prokaryotes to eubacteria, mushrooms, mollusks, insects, and others [19,20]. Furthermore, phosphonates form about 10% of the dissolved and particulate phosphorus in the oceans and appear to be key determinants of the productivity of marine phytoplankton [21]. These molecules most likely appear in the form of polysaccharides esterified with methylphosphonic acid and 2-hydroxyethylphosphonic acid [22].…”
Section: History Of Bisphosphonatesmentioning
confidence: 99%
“…Indeed, it has also been found that natural BPs, such as ciliatin or 2-aminoethylphosphonic acid (2-EPA), which are analogs of the amino acids β-alanine and aminosulfonate taurine, are quite common among different organisms, from prokaryotes to eubacteria, mushrooms, mollusks, insects, and others [19,20]. Furthermore, phosphonates form about 10% of the dissolved and particulate phosphorus in the oceans and appear to be key determinants of the productivity of marine phytoplankton [21]. These molecules most likely appear in the form of polysaccharides esterified with methylphosphonic acid and 2-hydroxyethylphosphonic acid [22].…”
Section: History Of Bisphosphonatesmentioning
confidence: 99%
“…Prochlorococcus and Synechococcus are the most abundant primary producers in the oligotrophic ocean and as such produce considerable amounts of semi-labile DOM; both can synthe-size phosphoenolpyruvate mutases (pepM), and therefore the DOM produced carries an enriched pool of MPn (Repeta et al, 2016;Sosa et al, 2019a). However, the metabolism of MPn is heavily regulated by bioavailable phosphate, and thus the metabolic pathway of pepM might be heavily downregulated in the subtropical North Atlantic, whereas under replete conditions, i.e., in the North Pacific, Prochlorococcus can allocate up to 40 % of its internal P quota to phosphonate synthesis (Acker et al, 2022). Yet, the trait to produce phosphonates is located on genomic islands, is subject to horizontal gene transfer and can be frequently exchanged among marine microbial communities.…”
Section: Methane Production Linked To Primary Productionmentioning
confidence: 99%
“…Hence, proteobacteria such Pelagibacter spp. in the SAR11 clade also obtain pepM and are able to produce phosphonates (Acker et al, 2022). Similarly, the trait of phosphonate consumption is subject to horizontal gene transfer, and high-light strains of Prochlorococcus carry both production and consumption traits.…”
Section: Methane Production Linked To Primary Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their abundance in nature, the biological role of phosphonolipids is poorly understood, though a protective function has been suggested (Kariotoglou & Mastronicolis, 1998). Specifically, the incorporation of phosphonate moieties in cell-surface structures has been suggested as a protective feature (Acker et al, 2022;White & Metcalf, 2007). Phosphonates in general are resistant to abiotic hydrolysis by low pH and withstand boiling in concentrated acid (Tamari & Kametaka, 1972).…”
Section: Introductionmentioning
confidence: 99%